Adaptive Leadership, Knowledge Management, And Human Capital Development: A Conceptual Framework for Public Sector Leadership Training and Organizational Resilience in the Post-Pandemic Era (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The post-pandemic environment has fundamentally transformed governance systems, public administration, and leadership practices worldwide. Public institutions increasingly confront complex adaptive challenges characterized by uncertainty, rapid technological change, evolving citizen expectations, and resource constraints. This thought paper examines how adaptive leadership, knowledge management, and human capital development collectively contribute to organizational resilience and public-sector effectiveness. Drawing upon adaptive leadership theory and contemporary public leadership scholarship, the paper argues that sustainable governance depends on leaders' capacities to mobilize learning, facilitate collaboration, and cultivate organizational adaptability. The paper advances an integrated conceptual framework positioning adaptive leadership as the strategic mechanism through which knowledge resources and human capital capabilities are transformed into institutional resilience. Furthermore, it highlights the implications of this framework for public-sector leadership training and development initiatives. By synthesizing insights from public leadership, knowledge management, and human capital literature, the paper contributes to emerging discussions on leadership development and organizational resilience in the new normal.